The effect of shock on stuttering - Hegde MN (Journal of All India Institute of Speech and Hearing, 1971)
The effect of aversive stimuli on stuttering has been an important area of investigation. This is largely due to the fact that such investigations are immediately relevant for developing more effective techniques for the modification of stuttering. Secondly, the effect of punishment on stuttering is of immense theoretical significance. Whether response contingent punishment will be able to suppress stuttering or will it result in an increase in the same behaviour is a factor of importance for a theoretical position on stuttering.